Lenalidomide in Pretreated Patients with Diffuse Large B‐Cell Lymphoma: An Italian Observational Multicenter Retrospective Study in Daily Clinical Practice. (2nd April 2019) - Broccoli, Alessandro; Casadei, Beatrice; Chiappella, Annalisa; Visco, Carlo; Tani, Monica; Cascavilla, Nicola; Conconi, Annarita; Balzarotti, Monica; Cox, Maria Christina; Marino, Dario; Goldaniga, Maria Cecilia; Marasca, Roberto; et al.
Abstract: Background: Diffuse large B‐cell lymphoma (DLBCL) is the most common non‐Hodgkin lymphoma subtype, and approximately 50% of the patients are >60 years of age. Patients with relapsed/refractory (rr) disease have a poor prognosis with currently available treatments. Lenalidomide is available in Italy for patients with rrDLBCL based on a local disposition of the Italian Drug Agency. Subjects, Materials, and Methods: An observational retrospective study was conducted in 24 Italian hematology centers with the aim to improve information on effectiveness and safety of lenalidomide use for rrDLBCL in real practice. Results: One hundred fifty‐three patients received lenalidomide for 21/28 days with a median of four cycles. At the end of therapy, there were 36 complete responses (23.5%) and 9 partial responses with an overall response rate (ORR) of 29.4%. In the elderly (>65 years) subset, the ORR was 33.6%. With a median follow‐up of 36 months, median overall survival was reached at 12 months and median disease‐free survival was not reached at 62 months. At the latest available follow‐up, 29 patients are still in response out of therapy. Median progression‐free survivals differ significantly according to age (2.5 months vs. 9.5 in the younger vs. elderly group, respectively) and to disease status at the latest previous therapy (15 months for relapsed patients vs. 3.5 for refractory subjects). Toxicities were manageable, even if 30 of them led to an early drug discontinuation. Conclusion: Lenalidomide therapy for patients with rrDLBCL is effective and tolerable even in a real‐life context, especially for elderly patients. Implications for Practice: Diffuse large B‐cell lymphoma (DLBCL) is the most common subtype of non‐Hodgkin lymphoma, and approximately 50% of the patients are >60 years of age. Patients with relapsed/refractory (rr) disease have a poor prognosis, reflected by the remarkably short life expectancy of 12 months with currently available treatments. The rrDLBCL therapeutic algorithm is not so well established because data in the everyday clinical practice are still poor. Lenalidomide for patients with rrDLBCL is effective and tolerable even in a real‐life context, especially for elderly patients. Abstract : This article reports an Italian observational retrospective study conducted on the use of lenalidomide in everyday clinical practice to determine if clinical trial results are confirmed in real‐life situations.